A STUDY OF TEENAGERS INTEREST IN LEARNING ENGLISH IN LANGSA - Lanya Tri Ratu; Fadlia Fadlia; Makhroji Makhroji; Surya Asra; Chairuddin Chairuddin (Universitas Samudra, 2020)
The background of this study is by the world of education that develops, demand every induvidual who in the circle of globalization education to paticipate in learning English. So that English is an important to learn.And to master an English, must be the interesting in self. From explanation above,the researcher interesting to take the title